The Treatment of Uncertainty and Learning in the Economics of Natural Resource and Environmental Management. (6th December 2017) - LaRiviere, Jacob; Kling, David; Sanchirico, James N; Sims, Charles; Springborn, Michael
Abstract: Environmental and resource economists often use models that include uncertainty and ways to reduce that uncertainty through learning. Using a standard environmental and resource economics framework, this article parses several different forms of uncertainty and learning that are commonly considered in the literature. We then review the applied theory literature using that framework to assess whether there is support for four hypotheses associated with uncertainty and learning in environmental management that have been raised in policy circles. We find that these hypotheses are often true for one type of uncertainty or learning but not another, highlighting how a lack of clarity can lead to confusion among researchers and policymakers.